Impact of Green Human Resource Management on Employee Green Behavior: The Mediating Role of Green Attitude - K. G. Priyashantha; Yogendran Priyangaa (Indonesian Journal of Sustainability Accounting and Management, 2022)
This study’s main objective was to examine the impact of Green Human Resource Management (GHRM) on green behaviors through the green attitude of employees. A sample of 150 employees from a chosen information technology company in Sri Lanka was drawn to accomplish this objective. The data were collected using a structured survey questionnaire, and the survey instruments were validated. The SPSS process macro was used to produce the expected impact findings. Results showed that the GRHM impacts green behaviors through employees’ green attitudes, indicating a partial mediation. The study concluded that organizations must engage in GHRM practices to strengthen employees’ green behaviors in implementing environmental and sustainability strategies. Theoretical implications of the study’s findings include validating the resource-based view, social identity theory, attitude theory, and measurement instruments used for the impact of GHRM on green behavior through green attitudes. The findings revealed GHRM’s contribution to the environmental management literature, particularly by creating new knowledge of the predicted impacts in the information and communication technology industry in a developing country context. This study also provides limitations and future research directions.